Fortified Extract of Red Berry, Ginkgo biloba, and White Willow Bark in Experimental Early Diabetic Retinopathy - Claudio Bucolo; Giuseppina Marrazzo; Chiara Bianca Maria Platania; Filippo Drago; Gian Marco Leggio; Salvatore Salomone (Journal of Diabetes Research)
Diabetic retinopathy is a complex condition where inflammation and oxidative stress represent crucial pathways in the pathogenesis of the disease. Aim of the study was to investigate the effects of a fortified extract of red berries, Ginkgo biloba and white willow bark containing carnosine and α-lipoic acid in early retinal and plasma changes of streptozotocin-induced diabetic rats. Diabetes was induced by a single streptozotocin injection in Sprague Dawley rats. Diabetics and nondiabetic (control) rats were treated daily with the fortified extract for the ten days. Retina samples were collected and analyzed for their TNF-α and VEGF content. Moreover, plasma oxidative stress was evaluated by thiobarbituric acid reacting substances (TBARS). Increased TNF-α and VEGF levels were observed in the retina of diabetic rats. Treatment with the fortified extract significantly lowered retinal cytokine levels and suppressed diabetes-related lipid peroxidation. These data demonstrate that the fortified extract attenuates the degree of retinal inflammation and plasma lipid peroxidation preserving the retina in early diabetic rats.